High temperature insulation

The silica-based inorganic fiber heat insulating material with cured silica and ceramic or metal components addresses the inefficiencies of existing materials by enhancing heat insulation, shape retention, and productivity in high-temperature applications.

JP7602285B2Active Publication Date: 2024-12-18IMAE KOUGIYOU KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023135385
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-07-09
Filing Date
2023-08-23
Publication Date
2024-12-18
Estimated Expiration
2039-07-03

AI Technical Summary

Technical Problem

Existing heat insulating materials made from inorganic fibers face challenges in forming three-dimensional shapes efficiently, require long molding times, and suffer from issues like radiant heat leakage and fiber scattering, which affect productivity and effectiveness in high-temperature applications.

Method used

A high-temperature heat insulating material composed of silica-based inorganic fibers with hydroxyl groups, using a cured silica material to fill gaps between fibers and incorporating ceramic particles or metal foils to reflect or absorb infrared radiation, allowing for rapid molding into three-dimensional shapes without compromising heat resistance.

Benefits of technology

The material provides excellent heat insulation and shape retention in high-temperature environments, reducing radiant heat leakage and fiber scattering, while maintaining productivity by shortening molding times to under 5 minutes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602285000004
    Figure 0007602285000004
  • Figure 0007602285000005
    Figure 0007602285000005
  • Figure 0007602285000006
    Figure 0007602285000006
Patent Text Reader

Abstract

To provide a high temperature heat insulation material having excellent adiabaticity even in a high temperature region of 600°C or higher.SOLUTION: A high temperature heat insulation material is a molding containing: a base material made of an entangled aggregate of silica-based inorganic fibers having hydroxyl groups; and a silica cured material that exists at a surface layer of at least one side of the base material so as to adhere to the surface of the silica-based inorganic fibers or fill or crosslink the inter-fiber gaps of the silica-based fibers. The silica cured material is a dry solidified product of colloidal silica having an average particle size of 1 to 200 nm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-temperature insulating material composed of an aggregate of inorganic fibers, which exhibits excellent heat insulating properties in the high-temperature range of 600° C. or higher. [Background technology]

[0002] Structures that become catalytic reaction systems under high temperatures, such as motorcycle and automobile manifolds, are generally covered with heat insulating materials in order to maintain the reaction efficiency at high temperatures and to prevent the effects of such high temperatures from reaching the outside. In recent years, nonwoven fabrics and mats made of inorganic fibers such as mineral fibers and glass fibers have been used as heat insulating materials for such structures because they are lightweight and flexible, and are installed by wrapping them around the target structure.

[0003] However, since the wrapping work is time-consuming, in recent years, in order to improve the ease of installation of the heat insulators and sound absorbing materials, and to improve heat retention efficiency and adhesion, there has been a demand in production sites for molded insulation materials that are molded to fit the external shape of the structure to which they are to be attached. In response to such demands, methods have been proposed in which a plate-shaped body such as a mat or blanket is molded, or inorganic fiber groups are directly molded.

[0004] Japanese Patent No. 4728506 (Patent Document 1) proposes a "method for producing a glass fiber molded product, in which glass fibers are compressed into a desired compressed shape and held at a temperature 10 to 100°C lower than their softening point to fuse the contact points between the glass fibers, and then the glass fibers are cooled to solidify the fusion and maintain the compressed shape." The above method is a method in which an aggregate of glass fibers (cotton-like or felt-like) is heated and pressurized to fuse the glass fibers together and form the glass fibers. In such fusion molding, at least the surface of the glass fiber needs to melt. In Patent Document 1, fusion molding is performed by heating at a high temperature at which the glass can melt for 10 minutes or more, such as 780°C for 30 minutes (first embodiment) and 780 to 810°C for 15 minutes (second embodiment). However, maintaining a high temperature of 700°C or more for 15 minutes or more is unacceptable in the production field because it is costly and hinders productivity improvement.

[0005] Furthermore, as a method of molding insulation material for use in high temperature regions, U.S. Patent No. 7,896,943 (Patent Document 2) proposes a method in which an aggregate (binderless) of silica-based glass fibers containing Al2O3 is set in a formwork and molded at 400 degrees Fahrenheit (204.4°C) to 1300 degrees Fahrenheit (704.4°C) for six minutes to heat-harden the fibers and produce a cone-shaped molded body. The silica-based glass fiber containing Al2O3 used here has heat resistance up to 2000 degrees Fahrenheit (about 1000°C) and is binderless, so it can provide molded articles that can be used for high-temperature insulation purposes. Regarding the heating time, it depends on the heating temperature, but it is disclosed that a molded body that retained the desired shape could not be obtained at 1112F (600°C) for 1 minute or at 700F (371°C) for 3 minutes (Table 1).

[0006] On the other hand, nonwoven fabrics and mats made of inorganic fibers such as mineral fibers and glass fibers are generally composed of an aggregate of short fibers, and therefore contain fibers that have become shorter during the manufacturing process, and so-called shot that has not been fiberized in the case of fiber mats made by the blowing method or spinning method. For this reason, in the case of nonwoven fabrics and mats made of inorganic fibers, there is a problem that shot and the like scatters during construction or use.

[0007] In order to solve these problems, it has been proposed to cover the surface of a substrate made of a fiber assembly, such as a nonwoven fabric or a mat, with a metal film. For example, Japanese Patent Application Laid-Open No. 2006-77551 (Patent Document 3) discloses a nonflammable heat insulating foam material in which a blended fiber material of polyester fibers and binder fibers having a lower melting point than the polyester fibers is entangled in a nonwoven fabric state and compression molded into a mat-like foam substrate, to which at least one side of the foam substrate is integrated a metal thin film layer via a binder agent layer. Although this non-flammable insulating foam material is made non-flammable by the aluminum foil layer, since the foam base material is made of polyester fiber, it cannot be used as an insulating material in high temperature ranges of 200°C or above.

[0008] As a fire-resistant heat insulating material applicable to a high-temperature heat source of 300°C or more, for example, JP 2017-71084 A (Patent Document 4) proposes a fire-resistant heat shielding sheet obtained by laminating a metal layer composed of a metal foil or a metal deposition film on both sides of a highly heat-resistant nonwoven fabric made of silica-based inorganic fibers having hydroxyl groups, and further storing the obtained laminate in a bag made of a woven silica fiber fabric. Based on the heat resistance of the highly heat-resistant nonwoven fabric as the base material and the bag, such a fire-resistant heat shielding sheet can be used even at 600°C. In addition, since the nonwoven fabric as an inorganic fiber aggregate is stored in the bag, there is no problem of short fibers scattering.

[0009] However, since the laminated state of the metal layer and the nonwoven fabric is achieved by storing them in a bag, if the bag is damaged, the laminated state cannot be stably maintained. In addition, the work of storing and sealing the laminate that is not fixed and integrated in the bag is troublesome, and from the viewpoint of productivity, a high heat-resistant insulating material that can be produced by a method that does not use a bag is desired. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Patent No. 4728506 [Patent Document 2] U.S. Patent No. 7,896,943 [Patent Document 3] JP 2006-77551 A [Patent Document 4] JP 2017-71084 A Summary of the Invention [Problem to be solved by the invention]

[0011] As described above, a heat insulating material composed of an aggregate of inorganic fibers can be used in high temperature regions and can also satisfy the requirement for flexibility. However, when it is desired to give a three-dimensional shape to an insulating material composed of an aggregate of inorganic fibers, binderless methods, such as fusion molding methods that utilize the fusion of glass fibers, take a long time to form the shape and are unsatisfactory in terms of productivity.

[0012] According to the thermoforming method using special glass fibers as proposed in Patent Document 2, it has become possible to shorten the molding time without impairing the inherent high-temperature resistance of the glass fibers, but molding within 5 minutes has not been achieved. From the viewpoint of productivity, it is desirable to keep the molding time to less than 5 minutes in production sites. Furthermore, in nonwoven fabrics and mats made of entangled fibers, the pore size and porosity are large, which causes problems such as leakage of radiant heat and the need for a large amount of energy to maintain a high temperature.

[0013] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a high-temperature insulating material that has excellent heat insulating properties even in a high-temperature range of 600°C or higher, and that can be formed into a three-dimensional shape that can be directly attached to a structure to be constructed. [Means for solving the problem]

[0014] The high temperature insulating material of the present invention has the following embodiments. (1) Silica-based inorganic fibers containing hydroxyl groups Filaments with fiber lengths of 30 to 200 mm but In the absence of organic bindersa substrate comprising an entangled aggregate; and a surface layer portion of at least one side of the substrate, the surface of the silica-based inorganic fiber being adhered to the surface of the silica-based inorganic fiber or the fiber of the silica-based inorganic fiber being adhered to the surface of the silica-based inorganic fiber. between The molded article contains a cured silica material that exists so as to fill or bridge gaps, and the cured silica material is a dried and solidified product of colloidal silica having an average particle size of 1 to 200 nm.

[0015] (2) In the embodiment (1), the silica cured material has an average particle diameter of 3 to 50 nm. , preferably 4 to 18 nm It is a dried and solidified colloidal silica in which spherical particles are individually dispersed.

[0016] (3) In the embodiment (1), the colloidal silica is an aggregate in which silica particles having an average primary particle size of 4 to 25 nm are associated in a chain or bead shape. Preferably, silica particles having an average primary particle size of 4 to 18 nm are aggregated in a chain shape and have an average particle size of 40 to 100 nm. It is.

[0017] (4) In the embodiment described in any one of (1) to (3), the aggregate has a bulk density of 90 to 160 kg / m 3 It is a nonwoven fabric, mat, or felt.

[0018] (5) The high-temperature insulating material according to any one of (1) to (4) above, wherein ceramic particles are dispersed in a surface layer portion of the base material. In this case, the ceramic particles is a silicon carbide, nitride, or boride having a thermal emissivity of 0.65 to 0.85 and an average particle size of 0.5 to 4 μm. It is preferable that:

[0019] (6) The high-temperature insulating material of the present invention is a three-dimensionally shaped article having the configurations of (1) to (5) above. Effect of the Invention

[0020] The high-temperature insulating material of the present invention can maintain the shape imparted to the substrate, which is an aggregate of silica-based inorganic fibers, by the silica cured material attached to the surface of the silica-based inorganic fibers or embedded or bridged in the gaps between the silica-based inorganic fibers. In addition, when ceramic particles as an infrared acting material are fixed and held in the substrate, the infrared acting material can reflect or absorb infrared rays that cause high heat, thereby preventing them from leaking out, so that in addition to the insulating effect based on the gaps (pores) between the fibers of the substrate, an excellent insulating effect can be obtained by preventing the leakage of radiant heat by the infrared acting material. [Brief description of the drawings]

[0021] [Figure 1] 1A to 1C are diagrams for explaining a manufacturing method of a three-dimensional molded body of a particle-dispersed type insulating material. [Diagram 2] FIG. 2 is a schematic diagram showing the configuration of a metal foil-attached type insulating material. [Diagram 3] 1A to 1C are diagrams for explaining a manufacturing method of a three-dimensional molded body of a metal foil-attached type insulating material. [Figure 4] FIG. 2 is a schematic diagram illustrating a method for evaluating heat insulation properties employed in the examples. [Diagram 5] FIG. 2 is a schematic diagram illustrating a method for evaluating shape retention employed in the examples. [Figure 6] 1 is a micrograph of a particle-dispersed type insulating material. [Figure 7] 1 is a micrograph taken of the substrate alone. [Figure 8] FIG. 2 is a schematic diagram for explaining the configuration of a metal foil-attached type insulating material prepared in the examples. [Figure 9] 1 is a photograph showing an example of a metal foil-attached type insulating material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The high-temperature insulating material of the present invention is a substrate made of an aggregate of entangled silica-based inorganic fibers having hydroxyl groups; and a molded article having a cured silica material present in a surface layer portion on at least one side of the substrate, the cured silica material being attached to the surface of the silica-based inorganic fibers or filling or bridging the interfacial gaps between the silica-based fibers, the cured silica material being a dried and solidified product of colloidal silica having an average particle size of 1 to 200 nm. Each component will be explained below.

[0023] [Base material] The substrate used in the present invention is an aggregate of silica-based inorganic fibers having hydroxyl groups. Specifically, it is an aggregate of entangled long or short fibers of silica-based inorganic fibers having hydroxyl groups, and includes nonwoven fabrics, mats, felts, etc. Among these, a mat (needle mat) in which fibers are entangled by needle punching to stabilize a plate-like body of a predetermined thickness is preferably used. The silica-based inorganic fibers constituting the substrate are not limited to one type, and may be a combination of two or more types of silica-based inorganic fibers.

[0024] The silica fiber having a hydroxyl group used as a constituent fiber of the substrate is preferably a silica fiber containing 0.1-20% Al2O3 and 80-99.9% SiO2. Such silica fiber is excellent in terms of affinity with water glass (sodium silicate solution) and silica particles used as the binder base material, and further with silicate used as a film-forming component.

[0025] The silica-based inorganic fiber having hydroxyl groups is a thermoformable glass fiber having 81% by weight or more of SiO2, and having Si(OH) present in a part of the SiO- network. Such hydroxyl groups are formed by reacting metal or metal oxide ions (e.g., Al) contained in the starting glass material with the starting glass material during the process of producing filaments or staple fibers from the starting glass material. 3+ , TiO 2+ or Ti 4+ , and ZrO 2+ or Zr 4+The hydroxyl groups contained in the silica fiber undergo a condensation reaction at approximately 600 to 800°C, as shown in the following formula (1), to form new siloxane bonds (Si-O-Si bonds) and release HO.

[0026] [ka]

[0027] A specific example of the composition of such silica-based inorganic fibers having hydroxyl groups is AlO 1.5 ·18〔(SiO2) 0.6 (SiO 1.5 OH) 0.4 A commercially available product may be used, for example, BELCOTEX (registered trademark) manufactured by belChem Fiber Materials GmbH.

[0028] BELCOTEX® fibers are generally made from silicic acid modified with alumina, and have an average fineness of about 550 tex for standard staple fiber pre-yarns. BELCOTEX® fibers are amorphous and generally contain about 94.5% by weight silica, about 4.5% by weight alumina, less than 0.5% by weight oxides, and less than 0.5% by weight other components. They have a mean diameter of about 9 μm with little variation in diameter, a melting point of 1500°C to 1550°C, and are heat resistant up to 1100°C.

[0029] Hydroxyl-containing silica fibers other than BELCOTEX can also be used by selecting appropriately depending on the purpose and area of ​​use.

[0030] The fiber diameter of the silica fiber is about 6 to 13 μm, preferably about 7 to 10 μm. The length of the inorganic fiber depends on the form of the substrate (felt, nonwoven fabric, blanket, sheet, etc.), but generally, staple fibers having a length of 1 to 50 mm, preferably 3 to 30 mm, or filaments having a length of about 30 to 200 mm, preferably 50 to 150 mm, are used.

[0031] When the substrate is a needle mat, the fiber length is preferably 30 to 130 mm, more preferably 45 to 100 mm, from the viewpoint of mat formability by needle punching.

[0032] The thickness of the sheet or plate-like body serving as the substrate is about 3 to 25 mm, preferably 3 to 12 mm, and more preferably 4 to 10 mm. When pressure molding is performed, if the sheet-like substrate is too thin, the final molded body may be too thin, and the desired heat insulating performance may not be ensured, and sufficient strength may be difficult to obtain. On the other hand, if the substrate is too thick, it tends to be difficult to maintain the shape of the molded body when it is given a three-dimensional shape.

[0033] The density of the base material is 80 kg / m 3 ~180kg / m 3 , more preferably 90 kg / m 3 ~160kg / m 3 If the density is too high, it becomes difficult to perform pressure molding. On the other hand, if the density is too low, the shape retention after molding decreases, and the strength of the final molded product becomes insufficient. In addition, the heat insulating properties also tend to decrease.

[0034] [Infrared acting material] An infrared acting material is capable of exerting a heat insulating effect by absorbing or reflecting infrared rays, mainly near-infrared rays (wavelengths of about 1 μm to about 4 μm), which are the cause of high-temperature thermal energy. Heat transfer is classified into three types: convection, thermal conduction, and radiation. Among these, the proportion of heat transfer by radiation increases at high temperatures of 500°C or higher. Therefore, it is effective for a heat insulating material used in a high temperature range of 500°C or higher, preferably 600°C or higher, and more preferably 800°C or higher, to prevent the radiant heat from the heat source from leaking to the outside. The infrared acting material used in the present invention can suppress the consumption of thermal energy near the heat source by reflecting the infrared rays radiated from the heat source to prevent them from leaking to the outside, or by absorbing and radiating the radiant heat from the heat source.

[0035] Specifically, (1) a metal foil having a thermal emissivity (ε) of 0.3 or less can be used as an infrared reflective type infrared acting material, or (2) ceramic particles having a thermal emissivity of 0.6 to 0.9 can be used as an infrared absorbing type infrared acting material. These will be described in detail below.

[0036] (1) Infrared reflective type infrared acting material As the infrared reflective type infrared acting material, a metal foil having a thermal emissivity of 0.3 or less, preferably 0.2 or less, more preferably 0.1 or less can be used. Metals having metallic luster can usually satisfy the thermal emissivity of 0.3 or less.

[0037] By covering one side of the heat insulating material with metal foil, infrared rays can be reflected and prevented from leaking to the outside. In this regard, metal vapor deposition films have the problem that pinholes may be present depending on the thickness of the vapor deposition film, and furthermore, pinholes are easily generated by three-dimensional molding. On the other hand, metal foil can form an infrared reflective layer without pinholes as long as it is not damaged, so it can exhibit excellent radiant heat reflection effect.

[0038] As for the metal that can be used, when the surface layer portion to be fixed and held is the heat source side, a metal having a melting point equal to or higher than the heat source temperature, and furthermore, a metal having a heat resistance comparable to that of the substrate is preferably used. Specifically, the metal has a melting point of 800°C or higher, preferably 1000°C or higher, more preferably 1200°C or higher, and even more preferably 1500°C or higher. On the other hand, when the metal is fixed and held on the surface layer (external side) opposite the heat source, the temperature of the external side is lower than the heat source temperature due to the insulating effect of the substrate, so the required heat resistance is lower than when used on the surface side. Therefore, although it depends on the heat source temperature and the type of substrate (particularly the thickness), it is also possible to use a metal with a melting point of 600°C or higher, or even 400°C or higher.

[0039] Examples of the metal foil that can be used include aluminum foil, silver paper, titanium foil, stainless steel foil, nickel foil, copper foil, phosphor bronze foil, brass foil, nickel silver foil, permalloy foil, Inconel foil, nichrome foil, molybdenum foil, zirconium foil, tantalum foil, tin foil, zinc foil, indium foil, niobium foil, lead foil, and plated iron foil. The metal foil to be used may be appropriately selected depending on the characteristics such as melting point, ductility, thickness, etc., and the type of heat insulating material to be applied. When forming into a three-dimensional shape, the metal foil is appropriately selected depending on the shape, especially the size of the R part.

[0040] Among the above metal foils, aluminum foil, gold foil, copper foil, stainless steel foil, molybdenum foil, and Inconel foil are preferably used from the viewpoint of thermal emissivity of 0.3 or less and ductility. Metal foils that are not oxidized and have a mirror-like luster and whose surface is not subjected to a matte finish are preferably used from the viewpoint of low thermal emissivity.

[0041] The thickness of the metal foil is 5 to 150 μm, preferably 10 to 100 μm, and more preferably 20 to 50 μm. If the thickness is less than 5 μm, the foil is too thin and easily torn, and is difficult to handle. On the other hand, if the thickness exceeds 150 μm, the foil is too thick, and the malleability and three-dimensional formability are reduced.

[0042] (2) Infrared absorbing type infrared acting material As the infrared absorbing type infrared acting material, ceramic particles having a thermal emissivity of 0.6 to 0.9, preferably 0.65 to 0.85, can be used.

[0043] As such ceramic particles, particles having an average particle diameter measured by a light scattering method of 0.5 to 4 μm, preferably 1 to 3 μm, and more preferably 1 to 2.5 μm are used. Furthermore, as the particle diameter distribution, the cumulative 90% diameter (D 90 ) is 10 μm or less, preferably 8 μm or less, and more preferably 7 μm or less. Ceramic particles of this size absorb infrared rays, particularly near infrared rays, and then emit them. Therefore, by fixing and holding an infrared absorbing type infrared acting material in the surface layer close to the heat source, it is possible to suppress the loss of thermal energy from the heat source.

[0044] Since the ceramic particles are fixed and held in the vicinity of the heat source, it is preferable that the ceramic particles used as the infrared ray acting material are ceramic particles that are difficult to oxidize or melt even when used for a long period of time in a high temperature region, and ceramic particles such as carbides, nitrides, and borides having a high melting point of 1500°C or more are preferably used. Carbon graphite is an example of an infrared ray acting material with a high melting point and high thermal emissivity. However, in the case of carbon, the emissivity (ε) is usually high, exceeding 0.95, and since it hardly reflects infrared rays, there is a risk that only the carbon location will be overheated. On the other hand, carbon has a much higher thermal conductivity than silica-based fibers and ceramic particles, so when it reaches a high temperature, heat transfer by thermal conduction increases. In this regard, ceramic particles can appropriately reflect infrared rays due to the difference in refractive index with the fixed and held silica cured material, and their thermal conductivity is also smaller than that of metals and carbon, so that it is easy to obtain a heat insulating effect by absorbing and emitting infrared rays. However, if the ceramic particles become too large, they themselves will act as a heating element, so it is preferable to make them a size that is necessary and sufficient to absorb near-infrared rays.

[0045] Examples of ceramics that can be used as infrared absorbing infrared emitting materials include carbides such as WC, TiC, SiC, and ZrC; nitrides such as TiN, ZrN, and TaN; borides such as CrB, VB2, W2B5, WB, TaB, and MoB; and silicide particles such as TiSi, ZrSi, and WSi. In general, these ceramic particles have a melting point of 1500°C or higher, and carbides, nitrides, and borides have a melting point of 2000°C or higher, so they are preferred because they can be used in high temperature ranges based on the heat resistance of the substrate. Among these, silicon carbides, nitrides, and borides are preferred from the viewpoint of affinity with silica cured products, and SiC is more preferred.

[0046] Such ceramic particles are fixed and held on the surface layer of the substrate by being dispersed in the cured silica material, or by being attached to the surface of the silica-based inorganic fibers constituting the substrate, or by being held in the gaps between the fibers. From the viewpoint of stably fixing and holding the ceramic particles on the surface layer of the substrate by the silica cured product, the content of the infrared ray acting material (ceramic particles) relative to the silica cured product (corresponding to the colloidal silica solid content) is preferably 1 to 20% by weight, more preferably 2 to 15% by weight, and even more preferably 3 to 10% by weight. If the content is too low, the infrared ray absorption effect is not sufficiently obtained, and if the content is too high, aggregation is likely to occur, and the influence of the thermal conductivity of the ceramic itself is likely to be large.

[0047] [Hardened Silica] The cured silica material that holds the infrared radiating material is an inorganic polymer having SiO2 or Si-O-Si bonds (siloxane bonds). Specifically, it is a dried and solidified product of a silica powder dispersion liquid having film-forming properties, or a dried and solidified product of a silica colloidal solution such as colloidal silica. Such a cured silica material has heat resistance comparable to that of silica-based inorganic fibers, and can stably fix and hold an infrared ray acting material in a high temperature range.

[0048] (1) A dried and solidified dispersion of film-forming silica powder (film-forming silica-based binder) When a film-like infrared reflecting material (metal foil) is used as the infrared acting material, the silica cured material must act as a binder between the metal foil and the substrate. The film-forming silica powder dispersion liquid used as the silica-based binder is a viscous liquid or paste containing a film-forming component in a silica powder dispersion liquid, or a mixture of these with water glass.

[0049] (1-1) Silica powder dispersion Examples of silica powder include ground crystalline silica (quartz powder, silica sand, silica stone, moganite, cristobalite, etc.), amorphous silica (colloidal silica, precipitated silica, dry silica, fumed silica, etc.), and hydrated amorphous silica such as opal. The silica may be synthetic silica or a mineral product containing silica.

[0050] Examples of the dispersion medium that can be used include water, water glass, organic solvents (e.g., lower alcohols such as isopropanol, esters such as ethyl acetate, ethers such as ethylene glycol monopropanol and propylene glycol monomethyl ether, ketones such as methyl ethyl ketone and methyl isobutyl ketone, cycloalkanes such as cyclohexanone, and aromatic compounds such as toluene), mixtures of water and lower alcohols (methanol, ethanol, propanol, isopropanol, etc.), and mixtures of these. Of these, water glass is a concentrated aqueous solution of sodium silicate and has a syrup-like viscosity. Water glass can also function as a coating film-forming component, but due to its softening point, it is difficult to use it at temperatures above 700°C. Therefore, in the case of metal foil-attached type insulation materials used for applications above 700°C, it is preferable to use a silica-based binder using water or a mixture of water and a lower alcohol as the dispersion medium.

[0051] In addition to silica powder, the silica powder dispersion may contain ceramic powder such as alumina powder, as long as the content is within a range that does not affect adhesiveness (30% or less of the solid content in the dispersion, preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less).

[0052] The solid content in the silica powder dispersion is appropriately selected depending on the type of paste or dispersion. In particular, when the binder is applied to the substrate by coating, spreading, spraying, etc., the solid content is appropriately set so as to have a viscosity suitable for these working modes.

[0053] The silica powder dispersion may be a commercially available product that is marketed as a heat-resistant inorganic adhesive. Examples of the commercially available product include the BETACK series (BETACK#160CC, BETACK#900B, BETACK#900C, BETACK#1200, BETACK#1550B, BETACK#970, BETACK#1600S, BETACK#1800LB, BETACK#003, BETACK#870, BETACK#873) manufactured by Sakai Chemical Industry Co., Ltd.

[0054] (1-2) Film-forming component Layered silicate is used as a film-forming component that imparts film-forming properties to the silica powder dispersion liquid as described above. The silica powder dispersion liquid, particularly the dispersion liquid or paste using water as a dispersion medium, is dried and solidified, and the silica powder becomes an aggregate, so that the silica powder is easily broken down and dropped off due to impact, bending, abrasion, etc. In addition, when water glass is used as a dispersion medium, the glass may soften at high temperatures, and the retention force of the silica powder may decrease. In this respect, the layered silicate plays the role of a coating film-forming component, and thus the silica powder can be prevented from dropping off and scattering from the silica cured product.

[0055] Layered silicates, also known as phyllosilicates, are composed of SiO2 tetrahedrons connected to three oxygen atoms in common, forming a two-dimensional flat layer structure. Metals constituting the salt include aluminum, potassium, sodium, calcium, magnesium, and the like.

[0056] As the layered silicate, sodium silicate of xNa2·ySiO2 (y / x=2 to 3) is preferable, and smectite (saponite, hectorite, stevensite, montmorillonite), vermiculite group minerals, etc. can be used, and the smectite group is preferable. The film-forming component used in the present invention may be any component containing layered sodium silicate, and may be a synthetic layered silicate, a mineral such as a smectite or vermiculite group mineral, or bentonite containing such a mineral as a main component. In addition, the bentonite is not limited to natural bentonite, but may be bentonite that has been refined to remove impurities contained therein and to increase the purity of the main component, montmorillonite.Furthermore, it may be synthetic bentonite, for example, calcium bentonite converted into sodium bentonite by ion exchange.Bentonite is a general term for clays that contain montmorillonite as the main component. When dispersed in water, these layered silicates swell due to water absorption. In addition, the interlayer cations and water molecules become hydrated, and the layers separate into unit layers. By creating a hydration layer on the surface of the unit layers, the layered silicates exhibit viscosity, i.e., they have a thickening effect. Furthermore, when dispersed in water, they exhibit thixotropy, which means that they show high viscosity in the low shear region and decrease in viscosity in the high shear region.

[0057] The content of the film-forming components in the cured silica material is preferably 0.1 to 5% by weight, more preferably 0.5 to 4% by weight, and even more preferably 1 to 3% by weight. For the purpose of forming a coating film, an amount within the above range is sufficient; if the amount is too large, the viscosity increases, and the method of application to a substrate is limited to a coating method, etc., and workability tends to decrease.

[0058] The film-forming silica-based binder having the above composition is a fluid (dispersion, viscous liquid, or paste) having viscosity and thixotropy. After solidification, the layered silicate solidifies into a stable card structure. As a result of the silica-based binder, which is the main agent, drying and solidifying, the layered silicate fills the gaps between the generated silica aggregate particles, and it is considered that the silica particles are stably held within the solidified layer, thereby preventing the silica powder from scattering. The dried and solidified film-forming silica binder produces a hardened silica product in which the film-forming component forms a matrix. The silica particles dispersed in the matrix have the effect of bonding the silica-based inorganic fiber and the metal foil. In addition, when water glass is included, the silica-based inorganic fiber of the substrate can be bonded to the metal foil during the vitrification (solidification) process.

[0059] (2) Colloidal solution in which fine particles of silicic anhydride are dispersed (colloidal silica) Colloidal silica refers to a colloidal solution in which aggregates of silicon dioxide (SiO2) that have OH groups on their surface become colloidal particles through hydration and are dispersed in an aqueous dispersion medium.

[0060] As the dispersion medium, water, an organic solvent (for example, a lower alcohol such as isopropanol, an ester such as ethyl acetate, an ether such as ethylene glycol monopropanol, propylene glycol monomethyl ether, an ketone such as methyl ethyl ketone, methyl isobutyl ketone, a cycloalkane such as cyclohexanone, an aromatic compound such as toluene, or the like), a mixture of water and a lower alcohol (methanol, ethanol, propanol, isopropanol, or the like), or the like can be used. From the viewpoint of the working environment, however, an aqueous dispersion medium such as water or a mixture of water and a lower alcohol is preferably used.

[0061] The colloidal particles are made of amorphous silicon dioxide particles having SiOH groups and OH groups on the surface thereof. - The ions are stabilized by the coexistence of alkali ions (Na ions), and are stably dispersed in the aqueous dispersion medium. When such colloidal particles as dispersoids are heated, the dispersion medium evaporates and the SiOH groups present on the particle surface form new siloxane bonds, which causes the colloidal particles to integrate with each other (fusion of the colloidal particle surfaces), and they can function as a binder between the silica-based inorganic fibers that make up the base material.

[0062] The content (solid content) of silicon dioxide in the colloidal solution is about 5 to 60 mass%, preferably about 5 to 50 mass%, and more preferably about 10 to 40 mass%. In terms of the efficiency of the spraying method, the viscosity is preferably 300 mPa·s or less. If the content of silicon dioxide, i.e., the solid content rate, becomes too low, the amount of coating to ensure the amount of silicon dioxide necessary to maintain the shape of the molded body will increase. This is because the amount of energy required to evaporate water, which is the dispersion medium during heat molding, and therefore the heating time must be extended, which is disadvantageous in terms of improving productivity. Also, if the amount of coating on the plate-shaped body is insufficient, the strength of the final molded body will be insufficient.

[0063] On the other hand, if the content of silicon dioxide (solid content rate) becomes too high, the silicon dioxide powder remaining on the surface of the molded body after molding tends to increase. The silicon dioxide powder remaining on the surface of the molded body causes dust and reduces the handling workability. In addition, in the state of the suspension or dispersion before molding, the stability of the colloidal particles, which are the dispersoid, decreases and they tend to gel. In addition, since it is difficult to apply the spray method as a method of application to the substrate, a coating method or a coating method is applied, but in this case, the coating workability decreases and it becomes difficult for silicon dioxide to be impregnated into the inside of the plate-shaped body, and as a result, there is a risk that the binder function of maintaining the shape of the molded body cannot be fully exhibited.

[0064] The size (average particle diameter) of the colloidal particles is not particularly limited, but is 1 to 200 nm, preferably 2 to 100 nm, more preferably 3 to 50 nm, further preferably 4 to 25 nm, and particularly preferably 4 to 18 nm. When the particle diameter is large, the strength of the obtained molded body tends to decrease, probably because the number of particles is relatively decreased when the content is the same. In addition, the shape retention of the molded body also tends to decrease.

[0065] The average particle size referred to here refers to the average primary particle size of colloidal particles, and can be determined as a sphere-equivalent diameter by dynamic light scattering, Sears method, BET method, laser diffraction scattering method, etc. The measurement method may be appropriately selected depending on the size of the colloidal silica. For example, for fine particles of several tens of nm or less, it is preferable to use the BET method or laser diffraction scattering method. The measurement of particle size by dynamic light scattering method can be performed using a commercially available particle size distribution measuring device. The Sears method is a method described in Analytical Chemistry, vol. 28, pp. 1981-1983, 1956, and is an analytical method applied to the measurement of the average particle size of colloidal silica.

[0066] Colloid particles may exist not only in a state where spherical particles are individually dispersed, but also in a state where microparticles are aggregated. As the mode of aggregation, for example, the microparticles may be in a state where they are elongated and associated in a chain or a bead shape. Here, in the case of chain-like or bead-like aggregates, the fine silica particles may be associated in the elongated direction to form elongated chain-like secondary particles, or some of the silanol groups of the associated particles may be condensed and bonded to each other to form elongated secondary particles. In addition, the elongated shape is not limited to a straight line, and may be branched or partially network-like. In the case of chain-like, thread-like or bead-like particles, the average particle size includes the case where the particle size (secondary particle size) when assumed to be a sphere is within the above range. Such secondary particle size can be measured by dynamic light scattering. The average particle size of the colloidal primary particles (spherical particles) constituting the secondary particles is preferably 4 to 18 nm.

[0067] When the colloidal particles are aggregated or associated, a hard coating film is easily formed, and the three-dimensional shape of the applied coating tends to be excellent. On the other hand, when the average particle size is increased or the particles are associated or aggregated in a chain or bead shape, the proportion of the particles remaining on the surface of the molded body tends to increase, possibly because some of the chain or bead-shaped aggregated particles tend to remain on the surface without being impregnated into the inside of the plate-shaped body, and the amount of the particles remaining in powder form on the surface of the three-dimensional molded body tends to increase. Since an increase in the amount of powder remaining on the surface of the molded body causes dust, from the viewpoint of handling and workability, a colloidal solution in which the particle size of the dispersoid is small and spherical particles are individually dispersed is preferable.

[0068] Moreover, if the colloidal particles as the dispersoid become too large, they may be difficult to penetrate into the inside of the plate-like body composed of inorganic fibers, and as a result, the function as a binder necessary for maintaining the shape tends to decrease. From this viewpoint, the average particle size (primary particle size) of the colloidal silica is preferably small.

[0069] The stability of colloidal particles is generally susceptible to the influence of pH. From the viewpoint of preventing gelation, it is preferable that the colloidal particles are stabilized alkaline, specifically with Na ions. That is, the liquid property (pH) of the silica colloidal solution is related to the stabilization of the colloidal particles, and is usually alkaline (pH 8 to 11) when stabilized with Na ions. However, the amount of strong alkaline ions for stabilizing the colloidal particles may be reduced to be neutral to acidic (pH 4 to 7).

[0070] The specific gravity of the colloidal solution at 20° C. usually depends on the silica content, and when the silica content is within the above range, it is about 1.10 to 1.40, and preferably about 1.12 to 1.25. Furthermore, the viscosity at 25° C. is preferably 300 mPa·s or less, and more preferably 100 mPa·s or less. Generally, when the viscosity is high, the material is more likely to gel, and it becomes difficult to apply the material to a substrate by spraying, as described below. From the viewpoints of workability and productivity, the viscosity is preferably 80 mPa s or less, and more preferably 60 mPa s or less.

[0071] The colloidal silica used in the present invention, i.e., the colloidal solution of silicon dioxide, may contain small amounts (about 500 to 300 ppm) of divalent metals such as calcium, magnesium, Sr, Ba, Zn, Pb, Cu, Fe, Ni, Co, and Mn, and trivalent metals such as Al, Fe, Cr, Ti, and Y in the silica sol due to the method for producing the colloidal silica.

[0072] [Embodiments of high temperature insulation material] The high-temperature insulating material of the present invention, which is composed of the above-mentioned base material, infrared acting material, and silica cured product, can be classified into: (I) metal foil-attached type insulating material using an infrared reflecting type infrared acting material (metal foil) as the infrared acting material; (II) particle-dispersed type insulating material using an infrared absorbing type infrared acting material (ceramic particles); and (III) combined type insulating material using two types of infrared acting materials, an infrared reflecting type and an infrared absorbing type, in combination. Each type of insulating material will be described below together with the method for producing the three-dimensional shaped molded product.

[0073] <Method of manufacturing particle-dispersed type heat insulating material and three-dimensional molded product thereof> In particle-dispersed type insulation materials, a hardened silica material is present in the surface layer of the substrate, either adhering to the surfaces of the fibers that make up the substrate, or filling or bridging the gaps between the fibers of the substrate, and the ceramic particles can be fixed and held in place by the gaps between the fibers or the hardened silica material.

[0074] The three-dimensional shaped molded article of the particle-dispersed type heat insulating material can be produced by the following production method. The manufacturing method for a three-dimensional shaped molded body of a particle-dispersed type thermal insulation material includes the steps of: applying, coating, spraying, or impregnating one side of an aggregate of silica-based inorganic fibers (plate-shaped substrate) with a silica colloidal solution containing an infrared absorbing type infrared acting material (ceramic powder); and heating and pressurizing the substrate so that one side of the substrate becomes concave. Each step will be described below with reference to FIG.

[0075] (1) Application process of silica colloid liquid containing ceramic powder The application step is a step of applying, coating, spraying, or impregnating one side of a plate-like body (substrate) 1 made of an aggregate (fiber group) of silica-based fibers with a colloidal solution containing ceramic powder used as an infrared ray acting material. Which of these is to be adopted can be appropriately selected depending on the viscosity and solid content of the silica colloidal solution containing ceramic powder.

[0076] The application or coating can be carried out by a brush coating, a doctor blade, a roll coater method such as a gravure coater, etc.; screen printing using a squeegee; spray coating using an air spray gun, an airless hand spray, a pressure-fed automatic air spray, etc.; or a contact method in which only one side is brought into contact with a colloidal silica suspension. Among these, the spray method is preferable from the viewpoint of workability and productivity. For example, as shown in Fig. 1(a), a method of spraying a colloidal solution 2 from one side of a plate-like body 1 composed of an aggregate (inorganic fiber group) of silica-based inorganic fibers 1a can be mentioned. Fig. 1(b) shows a state in which a silica colloidal solution containing a particulate infrared acting material 2a is applied to one side of the plate-like body 1.

[0077] The amount of the silica colloid solution to be applied is appropriately selected according to the solid content of the suspension to be used. Therefore, the amount of application is 100 to 600 g / m2 in terms of the solid content per coating area of ​​the substrate. 2 Approximately, preferably 100 to 400 g / m 2 , more preferably 100 to 300 g / m 2 That's about it. If the coating amount (solid content) is too large, the silica colloid particles and ceramic powder are less likely to be impregnated into the molded body, and a silica film is more likely to form on one side (application surface) of the molded body. The hard silica film is less flexible and cushioned than an aggregate of inorganic fibers, so it tends to be less easy to install. In addition, the fixing and retention of the ceramic particles as an infrared ray acting material is also insufficient. On the other hand, even if a colloidal silica with a fine particle size that is easily impregnated into the inside of the plate-shaped substrate is used, if the coating amount is too large, the amount of silica remaining on the plate-shaped body surface increases, and as a result, the silica powder is more likely to remain on the surface of the molded body. Such silica powder causes dust, which reduces handling and workability.

[0078] If the concentration (solid content) is too low, the amount of colloidal solution required to achieve a given coating amount increases, which takes longer to dry and heat-set, resulting in reduced productivity. If the coating amount is reduced from the standpoint of productivity, the amount of silica that functions as a binder decreases, making it difficult to maintain the three-dimensional shape.

[0079] (2) Heating and pressurizing process The substrate to which the colloidal silica is applied is usually heated and pressed in a mold heated to a predetermined temperature. In this case, it is preferable to set the substrate so that the surface to which the colloidal silica solution is applied becomes the concave side of the desired three-dimensional shape. For example, as shown in Fig. 1(b), when a pair of dies consisting of a male die 5 and a female die 6 are used, they are set so that the convex surface of the male die 5 faces the colloidal silica application portion 2a. When the male die 5 is heated and pressurized in a pressed state, a three-dimensional molded body 7 (Fig. 1(c)) corresponding to the female die 6 is obtained.

[0080] The pressure to be applied is a pressure that results in a thickness reduction rate of the plate-shaped body, i.e., a thickness reduction amount (T1-T2) when the thickness of the final molded body is T2 (see FIG. 1(c)) relative to the initial thickness T1 (see FIG. 1(a)) of the plate-shaped body, of less than 50%, preferably approximately 5 to 45%, and more preferably approximately 10 to 40%. A large thickness reduction rate means that the compression rate of the plate-like body is large. If the compression rate is too large, the inorganic fibers constituting the plate-like body are more likely to recover elastically, resulting in a decrease in the shape retention of the molded body. In addition, from the viewpoint of heat insulation, the thicker the material, the better the heat insulation. On the other hand, if the thickness reduction rate is too low, that is, if the compression rate is too small, the proportion of fibers fixed will be low due to the relationship with the impregnation depth of the silica colloid particles into the plate-like substrate, and as a result, the shape retention will tend to be insufficient.

[0081] The heating temperature is 100 to 500°C, preferably 150 to 500°C, and more preferably 150 to 400°C. The heating temperature is a temperature necessary and sufficient to evaporate the dispersion medium (usually water) contained in the colloidal solution of silicon dioxide in a short time, and may be appropriately selected in relation to the heating time. The heating time can be shortened by increasing the temperature. When a high temperature of 600°C or higher is selected, the hydroxyl groups of the colloidal silica react to form siloxane bonds. On the other hand, when the silica fiber having a hydroxyl group, which is the constituent fiber of the plate-shaped body, is heated to 500°C or higher, the fiber hardens and causes physical irritation on the skin surface of the worker handling it, causing itching, etc., which causes a decrease in workability and handling. From this point of view, it is preferable to set the heating temperature to less than 500°C.

[0082] The pressurization and heating time depends on the average particle size and shape of the colloidal particles, the silica content in the colloidal solution, the amount applied, the viscosity of the suspension, and other factors. By using the silica colloid solution used in the present invention under the above conditions, it is possible to heat-set the material within 5 minutes, and even within 3 minutes, or even within 1 minute. If the heat-set is insufficient, the elastic restoring force of the fibers will prevent the material from retaining the pressure-molded shape. On the other hand, from the viewpoint of productivity, heating and pressing for more than 5 minutes is not preferable.

[0083] The shape of the molded product formed by molding may be a tray shape, a hemisphere shape, a pipe shape, a semicircular cross section shape, a truncated cone shape, or the like, but other shapes are also acceptable.

[0084] The three-dimensional shape of the insulating material is generally given by a press molding method using a press corresponding to the male mold 5 as shown in Fig. 1. However, it is also possible to use a thermoforming method (compressed air molding) in which a plate-like body is clamped between a female mold and a hot plate, air is blown in from the mold side to bring the sheet into contact with the hot plate and soften it, then the air blowing is stopped and compressed air is blown in from the hot plate to press it against the molding surface of the female mold, or a vacuum molding method in which the sheet is clamped to a frame suspended above the mold, heated and softened, then a vacuum is created between the sheet and the mold to bring the sheet into close contact with the mold, and the sheet is cooled as is to be molded into a three-dimensional shape. In either method, it is preferable to apply pressure so that the concave portions of the molded product (the convex surfaces of the mold) become the surfaces to be coated with colloidal silica, which requires only a small degree of expansion and contraction in an uneven three-dimensional shape.

[0085] In addition, when manufacturing a flat heat insulating material, it is not necessary to perform pressing using a mold. The heating and pressing process can be replaced by drying and solidifying the silica colloidal solution. However, heating is preferable to shorten the drying and solidifying time, and pressing is preferable to stably fix and hold the particulate infrared ray acting material.

[0086] The particle-dispersed type heat insulating material and its three-dimensional molded product as described above are used so that the surface on which the infrared-acting material is fixed faces the heat source. By absorbing and radiating radiant heat (infrared rays, particularly near-infrared rays) from the heat source near the heat source, the loss of thermal energy from the heat source can be suppressed.

[0087] <Metal foil-attached type heat insulating material and a method for manufacturing the three-dimensional molded product> Fig. 2 is a diagram showing the configuration of one embodiment of the metal foil-attached type heat insulating material of the present invention. A metal foil 4 is attached via a silica cured material layer 3 to one side (Fig. 2(a)) or both sides (Fig. 2(b)) of a substrate 1 composed of an aggregate of silica-based inorganic fibers having hydroxyl groups.

[0088] The metal foil-attached type heat insulating material can prevent infrared rays from leaking to the outside due to the radiant heat reflection effect of the metal foil 4 attached to the surface, and can exhibit excellent heat insulating effects. Furthermore, by forming the surface of the heat insulating material with metal foil, the handleability of the substrate is improved. That is, when the substrate is used alone as an aggregate of inorganic fibers, there are problems in that the fibers constituting the substrate are broken and dust particles such as shot contained in the substrate are scattered when the substrate is attached to a structure, but by attaching metal foil to the surface, these scatterings can be prevented and the handleability is improved. In particular, by attaching metal foil to the outer surface, dust generation from the substrate can be prevented, and foreign matter such as dirt and sand can be prevented from adhering to and entering from the outside world.

[0089] The attachment side of the metal foil must be selected according to the type of metal foil (melting point) used and the application of the insulation material. For example, aluminum foil (melting point of aluminum is 660°C) will melt and burn if exposed to a heat source of 600°C or higher for a long period of time, so it is preferable to have the metal foil attachment side facing outward. If the heat source temperature is below the melting point of the metal foil used, the metal foil can be applied to the heat source side.

[0090] The above-mentioned metal foil-attached type thermal insulation material can be produced by a method including the steps of applying, coating, spraying or impregnating a film-forming silica-based inorganic binder onto at least one surface of a substrate made of silica-based inorganic fibers having hydroxyl groups (see FIG. 3(a)); applying metal foil 4 to the binder-coated surface (see FIG. 3(b)); and drying and solidifying the binder.

[0091] A flat or sheet-shaped metal foil-attached type insulation material can be manufactured by a binder coating process, a metal foil attachment process, and a binder drying and solidifying process. When manufacturing a metal foil-attached type insulation material having a three-dimensional shape, the binder is solidified while being pressed using a mold when drying and solidifying the binder, thereby giving it a three-dimensional shape (see Figure 3(c)).

[0092] In other words, metal foil-attached insulation material having a three-dimensional shape can be manufactured by a method similar to the manufacturing method of particle-dispersed insulation material, including the steps of applying, coating, spraying or impregnating a film-forming silica-based binder 3' onto one side of a substrate 1; attaching metal foil 4 to the binder-coated surface; and heating and pressurizing using molding dies 5', 6'.

[0093] As with particle-dispersed type insulating materials, the three-dimensional shape to be imparted may be tray-like, hemispherical, pipe-like, semicircular in cross section, truncated cone-like, etc., depending on the mold used. Each step will be described below.

[0094] (1) Binder application process The application step is a step of applying, coating, or spraying the above-mentioned film-forming silica-based binder (silica powder dispersion or paste to which layered silicate is added) 3' onto one or both sides of a plate-like or sheet-like substrate 1 composed of an aggregate of fibers. Which of these is to be adopted can be appropriately selected depending on the viscosity and solid content of the film-forming silica-based binder to be used.

[0095] The coating, coating, and spraying methods can be the same as those for the particle-dispersed type heat insulating material. From the viewpoints of workability and productivity, it is preferable to use the spray method. From this viewpoint, the film-forming silica-based binder may be appropriately diluted with water before use.

[0096] The amount of binder applied is appropriately selected according to the solid content of the suspension used. Therefore, the amount of binder applied is 100 to 600 g / m2 in terms of the solid content per area of ​​the plate. 2 Approximately, preferably 100 to 400 g / m 2 , more preferably 100 to 300 g / m 2 That's about it. Since the cured binder (cured silica) has a higher thermal conductivity than the base material, if the amount of coating (solid content) is too large, the thermal conductivity of the cured silica can easily cause a deterioration in the heat insulation performance. On the other hand, if the amount of coating is too small, the adhesion of the metal foil becomes insufficient. When metal foil is attached to both sides of the substrate, a binder may be applied to both sides of the substrate.

[0097] (2) Metal foil attachment process A metal foil 4 is attached to the surface coated with the binder. When a molding die is used for pressurization and solidification, instead of placing the metal foil on the coated surface, the metal foil may be set in advance on the surface of the pressurizing die and the die may be pressed against the metal foil to attach the metal foil to the surface to which the binder is applied.

[0098] (3) Heating and pressurizing process When manufacturing a three-dimensional metal foil-attached type thermal insulation material, after attaching the metal foil, the material is heated and pressurized using molds 5', 6' (Fig. 3(c)). Specifically, the molds are heated to a predetermined temperature and pressed against the metal foil-attached substrate with a predetermined pressure. The binder dries and solidifies during the heating and pressing process.

[0099] The pressure and heating / pressurizing time for imparting a three-dimensional shape are the same as those for the particle dispersion type. That is, the pressure for imparting a three-dimensional shape is a pressure that makes the thickness reduction rate of the substrate, that is, the thickness reduction amount (T1-T2) when the initial substrate thickness T1 (see FIG. 3(a)) is the thickness of the final molded body T2 (see FIG. 3(d)), less than 40%, preferably about 5 to 35%, and more preferably about 10 to 30%. The heating temperature and time are preferably set appropriately depending on the type of binder and the amount of coating. The pressure, particularly the pressure speed, is preferably selected depending on the ductility of the metal foil from the viewpoint of the molding followability of the metal foil. Heating is preferable because it can shorten the time required for drying and solidifying. On the other hand, rapid heating at high temperatures can cause the solidified material to have a foam structure due to the rapid evaporation of the dispersion medium, which is likely to cause a decrease in adhesive strength. The presence or absence of heating, the heating temperature, and the heating time can be appropriately set depending on the productivity and application of the metal foil-attached type insulating material.

[0100] In Fig. 3, the surface to be pressed by the male die 5' is the surface to which the metal foil 4 is attached, but when the metal foil is attached to the outer peripheral surface of the semispherical molded body, the surface opposite to the surface to which the metal foil 4 is attached may be pressed by the male die. For example, in Fig. 3(c), the side to which the metal foil 4 is attached may be placed on the female die 6'.

[0101] <Combined type insulation material> A combined type insulation material is an insulation material that has metal foil attached to one side and infrared absorbing type infrared acting material (ceramic particles) fixed and held on the opposite side. This type of combined type heat insulating material is used so that the side on which the infrared absorbing type infrared acting material (ceramic particles) is fixed and held is the side closest to the heat source. In the combined type, the metal foil prevents the leakage of infrared rays and reflects them toward the heat source, while the ceramic particles absorb and radiate thermal energy from the heat source at a position close to the heat source, making it possible to suppress the consumption of thermal energy. Therefore, it is useful as a heat insulating material for heat sources in high temperature ranges.

[0102] <Three-dimensional shaped molded object> The heat insulating material having a three-dimensional shape produced as described above can stably fix and hold the three-dimensional shape by the silica cured product. That is, even if a silica fiber substrate is shaped by the elasticity of the fiber, it is difficult to stably hold and fix the shape due to springback, but since the binder solidified material (silica cured product) does not deform, springback can be suppressed even if the fibers constituting the substrate are not fused at high temperature.

[0103] The thickness of the three-dimensional molded body of either the metal foil-attached type heat insulating material or the particle-dispersed type heat insulating material depends on the initial thickness of the base material (fiber plate) used as the molding material, but is usually preferably 3 to 20 mm, more preferably 4 to 15 mm, and may be further 4 to 15 mm. As a heat insulating material used for weight reduction purposes, even with this thickness, the heat insulating effect can be obtained.

[0104] The density of the compact is 100 to 300 kg / m 3 is preferably 130 to 270 kg / m 3 A low density means that the fiber density in the molded body is low, which is likely to cause a decrease in thermal insulation performance. On the other hand, increasing the density of the molded body means that the fiber compression rate is excessively high, and the fiber density must be 300 kg / m 3 If the temperature exceeds this range, the fibers are likely to return to their original elastic state, and as a result, the three-dimensional shape of the molded article is less retained.

[0105] The high-temperature insulating material of the present invention can be used as a sound-absorbing material or cushioning material for use in high-temperature regions, in addition to its use as an insulating material, because the voids formed by the entanglement of the fibers constituting the base material can exhibit a vibration-reducing effect, depending on the thickness and density of the molded body and the type of fiber used as the constituent material.

[0106] Not only does it have heat resistance of 600°C or more, even 800°C to 1000°C, and has excellent heat insulation properties in high temperature ranges, but it also functions as a sound absorbing material and a buffer material, so it can be used as a sound absorbing and insulating material attached to the exhaust part of an automobile, especially near the manifold. The use of such a heat insulating material can suppress the temperature drop when the engine is stopped, and improve the reaction efficiency of the catalytic reaction at high temperatures, and therefore the engine efficiency, or the fuel efficiency of thermal equipment that operates at high temperatures, such as fuel cells. Conventionally, when used for such purposes, the heat insulating sheet was attached by wrapping it around the target structural member, but by forming it into a three-dimensional shape with a recess that matches the shape of the attachment part, it also leads to improved installation workability. EXAMPLES

[0107] [Comparison of the thermal insulation properties of high-temperature insulation materials] 1. Components of high temperature insulation materials (1) Base material BELCOTEX® 110 (composition: AlO 1.5 18[(SiO2) 0.6 (SiO 1.5 OH) 0.4A needle mat (length: 300 mm, width: 300 mm, thickness: 6 mm) was prepared by needle punching a group of fibers (fiber diameter: 9 μm, average fiber length: approximately 90 mm) into a mat shape.

[0108] (2) Infrared acting material (2-1) Infrared reflective type infrared acting material A 25 μm thick aluminum foil "My Foil" (product name) manufactured by UACJ Corporation was used. (2-2) Infrared absorbing type infrared acting material SiC powder from Nippon Keical Co., Ltd. (Particle size distribution measured by light scattering method: D 50 1.8μm, D 90 The SiC powder used had an emissivity of about 0.82.

[0109] (3) Silica hardening material (3-1) Film-forming silica-based binder The silica powder dispersion liquid used was the heat-resistant inorganic adhesive "BETACK900C" (alkaline viscous paste with approximately 50% crystalline silica and approximately 20% sodium silicate, viscosity 20-50 Pa·s) manufactured by Sakai Chemical Industry Co., Ltd. This was diluted with water to a weight ratio of 1:1, and then "Sumecton SA" (synthetic clay belonging to the smectite group) manufactured by Kunimine Kogyo Co., Ltd. was added as a film-forming component so that Sumecton SA was 2% by weight, and the mixture was stirred until uniform, to prepare a film-forming silica-based binder liquid.

[0110] (3-2) Colloidal silica (colloidal solution of silica) Snowtex XS (particle size 4-7) manufactured by Nissan Chemical Industries, Ltd. nm A colloidal solution in which silica particles (spherical) were dispersed in an aqueous dispersion medium (containing Na ions), SiO2 content 20%, neutral) was used as a binder.

[0111] 2. Manufacturing of high temperature insulation materials (1) Metal foil-attached type insulation material (No. 1, 2) The film-forming silica-based binder prepared above was sprayed onto one side of the needle mat as a substrate using an automatic gun. The amount of the suspension sprayed was 333 g / m2 per side. 2 It is. Aluminum foil (thickness 25 μm) was attached to the binder-coated surface and pressed in a heat press set at 300°C until the thickness was reduced by 35% (corresponding to a compression rate where the thickness after compression (T2) is 65%) when the original thickness (T1) was 100% at 300°C. After holding in this state for 1 minute, the heat press was released to create metal foil-attached type insulation materials No. 1 and 2, with metal foil attached to one side. The heat insulating properties of the prepared heat insulating materials were evaluated by the method described below. The results are shown in Table 1.

[0112] (2) Particle dispersion type insulation material (No. 3 to 5) SiC powder as an infrared absorbing type infrared acting material was added to colloidal silica so that the solid concentration was 5 wt %, 10 wt %, and 15 wt %, to prepare SiC-containing silica colloidal solutions. The above-prepared SiC-containing silica colloidal solution was sprayed onto one side of the needle mat as a substrate using an automatic gun. The amount of spray was 333 g / m2 of suspension per side. 2 (The same amount of binder liquid with different concentrations). After coating, the sheets were pressed in a heat press set at 300°C until the thickness was reduced by 35% (corresponding to a compression rate where the thickness after compression (T2) is 65%) when the original thickness (T1) was 100% at 300°C. After holding the sheet in this state for 1 minute, the heat press was released to create particle-dispersed type insulation materials Nos. 3 to 5, with the infrared-active material fixed and held on one side. The heat insulating properties of the prepared heat insulating materials were evaluated by the method described below. The results are shown in Table 1.

[0113] (3) Insulation materials using a combination of metal foil and ceramic particles (No. 6-8) The above-prepared SiC-containing silica colloidal solution was sprayed onto one side of the needle mat as a substrate using an automatic gun. The amount of spray was 333 g / m2 of suspension per side. 2(The same amount of binder liquid with different concentrations) A film-forming silica-based binder was sprayed onto the opposite side of the substrate using an automatic gun, and then aluminum foil was attached. In this state, pressure was applied in the same manner as for Nos. 1 to 5 using a hot press set at 300°C, and combined type insulation materials Nos. 6 to 8 were created, in which SiC was fixed and held on one side and metal foil was attached to the opposite side. The heat insulating properties of the prepared heat insulating materials were evaluated by the method described below. The results are shown in Table 1.

[0114] (4) Reference examples 1 and 2 As Reference Example 1, the base material alone was pressed in the same manner as in No. 1 to produce a thermal insulating material. As Reference Example 2, only the colloidal silica used in No. 3 (a silica colloidal solution not containing SiC) was sprayed and pressed in the same manner as in No. 3 to produce a thermal insulating material. The heat insulating properties of the prepared heat insulating materials were measured and evaluated, and the results are shown in Table 1.

[0115] 3.Insulation evaluation The heat insulating properties of the high-temperature heat insulating materials Nos. 1 to 8 and Reference Examples 1 and 2 prepared above were evaluated using a measuring device shown in FIG. That is, an opening 10a with a diameter of 100 mm was opened on the upper surface of a heating furnace 10 equipped with a heater 11, and the prepared heat insulating material 13 was placed on this opening 10a. The heat insulating material 13 was placed so that the surface on which the infrared ray acting material was fixed and held was the heat source side (heating furnace side) or the outside world side, as shown in Table 1. A metal (SUS304) plate 14 with a length x width x thickness of 150 mm x 150 mm x 1.5 mm was placed as a weight on the upper surface (the surface opposite to the heat source side) of the heat insulating material 13. The surface of the metal plate 14 was sprayed with black body (manufactured by Ichinen TASCO Co., Ltd., emissivity 0.94). The inside of the heating furnace 10 was heated by the heater 11, and the temperature was controlled by the thermocouple 12 to be set at 600°C or 900°C. After each set temperature was reached, it was left for 30 minutes. After 30 minutes, the surface temperature of the metal plate 14 was measured using a thermal camera (FLIR640T). The measurement results are shown in Table 1.

[0116] [Table 1]

[0117] In No. 1, the aluminum foil was burned away at 900°C, making measurement impossible. At about 600°C, no heat insulating effect was observed in any of Nos. 2 to 8 compared to the substrate alone (Reference Example 1), but at 900°C, all of them showed a greater heat insulating effect than the substrate alone. In addition, a comparison of Nos. 3 to 5 with Nos. 6 to 8 shows that a higher heat insulating effect can be obtained by combining an infrared absorbing type infrared acting material with an infrared reflecting type infrared acting material than by using only the infrared absorbing type. When the heat source temperature becomes high, a higher heat insulating effect can be expected by fixing and holding an infrared absorbing type infrared acting material on the heat source side and an infrared reflecting type infrared acting material on the outside world side.

[0118] [Relationship between silica colloid particles and three-dimensional shape formability] 1. Components of high temperature insulation materials (1) Base material A technical needle mat (isoTHERM (registered trademark) BCT) from Frenzelit (size: length x width x thickness 300 mm x 300 mm x 6 mm) was used. The needle mat is made of BELCOTEX® 110 (composition: AlO 1.5 18[(SiO2) 0.6 (SiO 1.5 OH) 0.4 ], a group of fibers with a fiber diameter of 9 μm is formed into a mat shape using the needle punch method, and the mat has a nominal thickness of 6 mm.

[0119] (2) Colloidal silica Colloidal silica having the average particle size and shape shown in Table 2 (all Na-type Snowtex (registered trademark) from Nissan Chemical Industries, Ltd.) was used. All were suspensions in which colloidal particles were stabilized with Na ions. Chain colloidal silica is a thread-like aggregation of silica particles with a primary particle diameter of 9 to 15 nm. Beaded colloidal silica is a beaded aggregation of silica particles with a primary particle diameter of 18 to 25 nm. These average particle diameters shown in Table 2 are the average particle diameters of secondary colloidal particles measured by dynamic light scattering.

[0120] 2. Manufacturing of three-dimensional shaped bodies No. 11 to 17 The colloidal silica shown in Table 2 was sprayed onto one side of the needle mat as a substrate. The amount of sprayed was 666 g / m2 as a suspension. 2 (Solid content: 133-320g / m 2 ). Next, as shown in Fig. 1(b), the side with the colloidal silica attached was placed on the upper surface of the mold on a female mold 6 set at 300°C, and pressed by a heat press 5 attached to the upper surface set at 300°C to a thickness reduction rate of 35% (corresponding to a compression rate where the thickness after pressing (T2) is 65%) when the original thickness (T1) is 100% at 300°C, as shown in Fig. 1(b), and the product was held in this state for 1 minute, after which the male mold (heat press) 5 was released to produce a tray as shown in Fig. 1(c). The distance (d1) between the side walls of the three-dimensionally shaped molded product 7 immediately after molding was 150 mm, and the inclination angle α of the side walls with respect to the horizontal plane was 70°. The shape retention and handling properties of the prepared trays were evaluated by the methods described below. The results are shown in Table 2.

[0121] Reference examples 11 and 12 Without using colloidal silica, the substrate alone was held at 300° C. under a pressure such that the thickness after pressing was 65% (thickness reduction rate: 35%) for 1 minute (Reference Example 11) or 5 minutes (Reference Example 12) to produce a tray-shaped molded body as shown in FIG. 1(c). The shape retention and handling properties of the prepared trays were evaluated. The results are shown in Table 2.

[0122] 3. Evaluation method and results (1) Shape retention As shown in Fig. 5, with the bottom surface of the prepared tray-shaped molded body fixed, a guide roller with a load (w) was applied to the side wall of molded body 20, and the side wall was inclined according to the magnitude of the load (W) (in Fig. 5, molded body 20' with an inclined side wall is shown). The amount of movement (x) of the bearing roller (diameter 32 mm, height from the bottom surface of the molded body 34 mm) corresponding to the load was measured, and the amount of movement x was defined as the amount of displacement x (unit: mm) based on the load and evaluated according to the following criteria. The measurement was performed on three molded bodies, and the evaluation was based on the average value. Displacement per 10g is less than 1mm: Best (◎) Displacement per 10g is 1mm to less than 2mm: Good (○) Variation per 10g is 2mm~5mm: No problem (△) Mutation amount > 3mm per 10g: Poor (×)

[0123] (2) Ease of use The surface of the molded article coated with colloidal silica was visually observed to see whether powder that could cause dust was generated, and the surface of the molded article coated with colloidal silica was touched with a hand to see how much powder adhered to the hand. The sample was rated as "△" when a large amount of powder was generated and the powder was noticeable when touched with the hand, "◯" when powder was generated but the amount of powder that adhered to the hand when touched with the hand was not enough to cause a problem, and "◎" when no powder was observed at all.

[0124] [Table 2]

[0125] As can be seen from a comparison of Nos. 11, 12, and 15, the shape retention decreased as the average particle size of the colloidal particles increased. Also, in the case of colloidal particles aggregated into chains, shape retention tended to be higher than in colloidal silica in which spherical particles were dispersed alone (No. 16).However, in the case of aggregated colloidal silica, a large amount of powder remained on the surface of the molded product, and the powder adhered to the hands when touched, making it difficult to handle (No. 16, 17).

[0126] When colloidal silica was not used, it was difficult to maintain the shape of the tray even after heating and pressing for 1 minute. When the heating and pressing time was increased to 5 minutes, the tray shape was maintained, but the retention was inferior to that when colloidal silica was used.

[0127] The surfaces of the recesses of the obtained three-dimensionally shaped molded bodies No. 11 and Reference Example 11 were observed under a microscope (magnification: 500 times) and photographed. The photographed micrographs are shown in Fig. 6 and Fig. 7, respectively. Compared with Fig. 7 (Reference Example 11), Fig. 6 (No. 11) shows that the fibers are crosslinked in places, and it was confirmed that the colloidal silica plays a role in binding the fibers together. Furthermore, in Fig. 6, the crosslinks of the colloidal silica were densely observed in the surface layer where the colloidal silica was applied, but almost no crosslinks were observed inside.

[0128] (4) Reference example 13 Instead of colloidal silica, isocyanate (Daiei Sangyo's blocked polyisocyanate "Blonate" (registered trademark)) was used, and 30% of the needle mat weight in solid content was sprayed onto one side of the plate, followed by heat and pressure molding under the same conditions as for No. 11. The surface of the molded product adhered to the convex surface of the male mold, making it difficult to release the molded product from the male mold. When the molded product was peeled off from the convex surface of the male mold, some of the fibers were found to be stuck to the convex surface.

[0129] [Manufacturing three-dimensional molded bodies of metal foil-attached type insulation materials] The film-forming silica-based binder prepared for producing the above-mentioned heat insulating material No. 1 was sprayed onto one side of the above-mentioned needle mat as a substrate using an automatic gun. The spray amount was 333 g / m as a suspension. 2A metal foil (thickness: 25 μm) was attached onto the binder-coated surface. Next, as shown in Fig. 3(c), the side with the metal foil 4 attached was set on the female mold 6' set at 300°C so that it was on the upper side of the mold, and pressed by a male mold 5' attached to the upper side and set at 300°C to a thickness reduction rate of 35% (corresponding to a compression rate where the thickness after pressing (T2) is 65%) when the original thickness (T1) is 100% at 300°C. After holding this state for 1 minute, the male mold (heat press) was released to produce a tray as shown in Fig. 8. The inclination angles of the side walls with respect to the horizontal plane were α = 70° and β = 85°.

[0130] A photograph of the prepared tray is shown in Figure 9. It was confirmed that the aluminum foil was evenly attached to the inside surface of the tray, and a stable tray shape was given to it. [Industrial Applicability]

[0131] The high-temperature insulating material of the present invention exhibits excellent heat insulating properties in high-temperature ranges of 600° C. or higher, based on the silica-based inorganic fiber mat as the substrate and the infrared ray acting material fixed and held on the surface layer of the substrate. In addition, since it retains the inherent heat resistance of the inorganic fiber as a constituent element of the molded product, it is useful not only as an insulating material used for high-temperature holding applications (e.g., catalytic converters), but also as a sound absorbing material, a buffer material, etc. used in high-temperature ranges. Furthermore, the method for producing a three-dimensional shaped product of the present invention can produce a three-dimensional shaped product that fits the installation location in a short time of less than 5 minutes, which helps to improve productivity for both the site where the product is manufactured and the user of the product (the site where the product is installed). Since the product can be directly set on a structure such as a muffler or fuel cell of a vehicle body, the installation burden at the installation site is reduced, which is useful.

[0132] Furthermore, when metal foil is used as an infrared-active material, it is possible to prevent dust generation from the silica-based inorganic fibers that make up the base material, scattering of powder and microfibers, and adhesion and intrusion of foreign matter from the outside world, making it possible to use it for insulation in structures used in high-temperature environments exposed to dust and dirt from the outside world, such as building structures and mufflers and silencers for vehicle exhaust systems. [Explanation of symbols]

[0133] 1 Base material 1a Silica fiber 2. Ceramic powder-containing silica colloidal solution 3. Hardened Silica 3' Film-forming silica-based binder 4 Metal foil 7,7' Three-dimensional shaped molded object

Claims

1. A substrate comprising an aggregate of entangled filaments having a fiber length of 30 to 200 mm and made of silica-based inorganic fibers having hydroxyl groups in the absence of an organic binder; and a cured silica material that is attached to the surface of the silica-based inorganic fibers or that is present in a surface layer portion on at least one side of the substrate so as to fill or bridge the interfiber gaps of the silica-based inorganic fibers; wherein the cured silica product is a dried and solidified product of colloidal silica having an average particle size of 1 to 200 nm.

2. 2. The high-temperature insulating material according to claim 1, wherein the hardened silica is a dried and solidified colloidal silica in which spherical particles having an average particle diameter of 4 to 18 nm are individually dispersed.

3. 2. The high-temperature insulating material according to claim 1, wherein the colloidal silica is an aggregate having an average particle size of 40 to 100 nm in which silica particles having an average primary particle size of 4 to 18 nm are associated in a chain shape.

4. The high temperature insulating material according to claim 1, wherein the aggregate is a nonwoven fabric, a mat, or a felt having a bulk density of 90 to 160 kg / m 3 .

5. The high-temperature insulating material according to claim 1, which is a three-dimensional shaped molded article.

6. The high-temperature insulating material according to any one of claims 1 to 5, wherein particles of silicon carbide, nitride, or boride having a thermal emissivity of 0.65 to 0.85 and an average particle diameter of 0.5 to 4 μm are dispersed in the surface layer of the base material.

Citation Information

Patent Citations

  • Nonflammable thermal insulation foam material and its manufacturing method

    JP2006077551A

  • Light-weight inorganic fiber molded body and method for producing the same

    JP2011208344A

  • Multi-layer fireproof material

    JP2013510742A

  • Fireproof heat insulation system, and fireproof heat insulation sheet using the same

    JP2017071084A

  • Method for molding glass fiber molded products

    JP4728506B2